Hepatic gene expression profiles during fed–fasted–refed state in mice - Ji, Nana; Xiang, Liping; Zhou, Bing; Lu, Yan; Zhang, Min (Frontiers in Genetics, 2023)
Regulation of nutrient status during fasting and refeeding plays an important role in maintaining metabolic homeostasis in the liver. Thus, we investigated the impact of the physiological fed–fasted–refed cycle on hepatic gene expression in nutrient-sensitive mice. We performed transcriptomic analysis of liver samples in fed, fasted and refed groups of mice. Through mRNA-sequencing (RNA-Seq) and miRNA-Seq, we compared fasted and fed states (fast versus fed cohort) as well as refed and fasted states (refed versus fast cohort) to detect dynamic alterations of hepatic mRNA–miRNA expression during the fed–fasted–refed cycle. We found dozens of dysregulated mRNAs–miRNAs in the transition from fed to fasted and from fasted to refed states. Gene set enrichment analysis showed that gene expression of the two cohorts shared common pathways of regulation, especially for lipid and protein metabolism. We identified eight significant mRNA and three miRNA clusters that were up–downregulated or down–upregulated during the fed–fasted–refed cycle. A protein–protein interaction network of dysregulated mRNAs was constructed and clustered into 22 key modules. The regulation between miRNAs and target mRNAs was presented in a network. Up to 42 miRNA–mRNA-pathway pairs were identified to be involved in metabolism. In lipid metabolism, there were significant correlations between mmu-miR-296-5p and Cyp2u1 and between mmu-miR-novel-chr19_16777 and Acsl3. Collectively, our data provide a valuable resource for the molecular characterization of the physiological fed–fast–refed cycle in the liver.